ANALISIS KETENTUAN HUKUM PELAKU PEMBUNUHAN SATWA DALAM FATWA MUI NOMOR 04 TAHUN 2014 DAN QANUN ACEH NOMOR 11 TAHUN 2019 - Junaidi Junaidi (SYARIAH: Journal of Islamic Law, 2023)
This thesis analyzes the provisions of legal sanctions and animal protection due to the increasing cases of wildlife killings in Aceh that threaten the existence of endangered animals such as Sumatran tigers, elephants, one-horned rhinos, and hornbills. To prevent this, further regulation is needed through Aceh Qanun Number 11 of 2019 concerning wildlife management and MUI Fatwa Number 04 of 2014 concerning Endangered Wildlife Conservation to Maintain Ecosystem Balance. There are two issues that are the focus of research, namely legal sanctions against perpetrators of killing protected animals in Aceh Qanun Number 11 of 2019 and MUI Fatwa Number 04 of 2014 and a review of ta'zir theory on these legal sanctions. In answering these problems, the author uses two theoretical frameworks, namely the theory of legislation and the theory of ta'zir as the authority of ulil amri, as well as the research method of normative legal studies with descriptive analysis. The results showed that criminal sanctions in Aceh Qanun Number 11 of 2019 concerning Wildlife Management in Aceh and MUI Fatwa Number 04 of 2014 concerning Endangered Wildlife Conservation to Maintain Ecosystem Balance can be explained in terms of law, prohibited acts, and criminal sanctions. In addition, the concept of criminal sanctions in the Aceh Qanun is closely related to the definition of ta'zir as a form of punishment that is flexible and can be adapted to certain social conditions and circumstances that cannot be specifically regulated in Islamic law. Therefore, this research is expected to make an important contribution to the development of legal theory and law enforcement practice in handling cases of killing protected animals in Aceh by revising the regulations.